Simulation of the Motion of Charged Particles in an Ablative Pulsed Plasma Thruster at the Initial Stage of the Discharge. (2017) - Antipov, A.A.; Bogatyy, A.B.
Abstract: A basic scheme of an ablation pulsed plasma thruster with rail geometry and a side feed of the propellant bar is considered. For such geometry, a theoretical description of the initial stage of the vacuum discharge, which would serve to explain the experimental results, does not exist. It was demonstrated experimentally that the configuration of the discharge channel depends essentially on the initial stage of discharge. A model of the motion of charged particles in the inhomogeneous electric and magnetic fields was developed. Due to the low plasma density at the initial stage of discharge, the model of the charged particles motion in electric and magnetic fields is described well by differential equations.